Recommendations on generic names competing for use in Leotiomycetes (Ascomycota) - Johnston, Peter R; Seifert, Keith A; Stone, Jeffrey K; Rossman, Amy Y; Marvanová, Ludmila (IMA fungus, 2014)
In advancing to one scientific name for fungi, this paper treats genera competing for use in the phylogenetically defined class Leotiomycetes except for genera of Erysiphales. Two groups traditionally included in the so-called "inoperculate discomycetes" have been excluded from this class and are also not included here, specifically Geoglossomycetes and Orbiliomycetes. A recommendation is made about the generic name to use in cases in which two or more generic names are synonyms or taxonomically congruent along with the rationale for the recommendation. In some cases the recommended generic name does not have priority or is based on an asexual type species, thus needs to be protected and ultimately approved according to Art. 57.2 of the International Code of Nomenclature for algae, fungi and plants (ICN). A table is presented listing all competing generic names and their type species noting the recommended generic name. New combinations are introduced for the oldest epithet in the recommended genus including Ascocalyx berenice, Ascoconidium purpurascens, Ascocoryne albida, A. trichophora, Blumeriella filipendulae, B. ceanothi, Botrytis arachidis, B. fritillariae-pallidoflori, Calloria urticae, Calycellina aspera, Dematioscypha delicata, Dermea abietinum, D. boycei, D. stellata, Diplocarpon alpestre, D. fragariae, Godroniopsis peckii, Grovesinia moricola, Heterosphaera sublineolata, Hyphodiscus brachyconium, H. brevicollaris, H. luxurians, Leptotrochila campanulae, Monilinia polystroma, Neofabraea actinidae, N. citricarpa, N. vagabunda, Oculimacula aestiva, O. anguioides, Pezicula brunnea, P. californiae, P. cornina, P. diversispora, P. ericae, P. melanogena, P. querciphila, P. radicicola, P. rhizophila, Phialocephala piceae, Pilidium lythri, Rhabdocline laricis, Streptotinia streptothrix, Symphyosirinia parasitica, S. rosea, Unguiculariopsis caespitosa, and Vibrissea laxa.
Keywords: Article 59; inoperculate discomycetes; taxonomy; one fungus–one name; nomenclature; unit nomenclature; Fungi; pleomorphic fungi; Ascomycetes